An evaluation of toxicity in essential oils of Geraniol, Geranial acetate, Gingerol and Eugenol in rats - seema farhath; P P Vijaya; M Vimal (International Journal of Phytomedicine, 2012)
The present study was carried out to investigate the effects of essential oils geraniol, geranial acetate, eugenol and gingerol on biochemical parameters in rats. Male rats were treated with 5 mL/Kg/day of essential oil in ethanol as vehicle for 14 consecutive days. Rats in the treated groups showed a more pronounced increase in body weight in comparison to control rats after 14 days and the biochemical (glucose, urea, creatinine, SGOT and SGPT) were observed and the rat was sacrificed and its stomach was taken out, opened and examined for macroscopic haemorrhagic gastric lesions. The results suggested that the biochemical parameters,geraniol and geranial acetate caused a significant increase in the levels of Glucose and Urea whereas there is a decreased level of glucose and urea in Gingerol and Eugenol and The level of creatinine differ slightly between the rats of control and treated groups and no haemorrhagic lesions were found.